Bullying in schools: the state of knowledge and effective interventions - Menesini E; Salmivalli C (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
During the school years, bullying is one of the most common expressions of violence in the peer context. Research on bullying started more than forty years ago, when the phenomenon was defined as aggressive, intentional acts carried out by a group or an individual repeatedly and over time against a victim who cannot easily defend him- or herself'. Three criteria are relevant in order to define aggressive behaviour as bullying: (1) repetition, (2) intentionality and (3) an imbalance of power. Given these characteristics, bullying is often defined as systematic abuse of power by peers. It is recognised globally as a complex and serious problem. In the present paper, we discuss the prevalence, age and gender differences, and various types of bullying, as well as why it happens and how long it lasts, starting from the large surveys carried out in western countries and to a lower extent in low- and middle-income countries. The prevalence rates vary widely across studies; therefore, specific attention will be devoted to the definition, time reference period and frequency criterion. We will also focus on risk factors as well as short- and long-term outcomes of bullying and victimisation. Finally, a section will be dedicated to review what is known about effective prevention of bullying.